True spies ebook - Galen, Shana (Lord and Lady Spy, 2013)
He's Getting Tired of Deception...She Wants a Little Intrigue Baron Winslow Keating is honor-bound to finish one last mission as an elite spy for the Barbican group even though he just wants to go home and be with his family. But after years of secrecy and absence, his daughters hardly know him and his wife has given up on him. Lady Elinor has had enough of domestic boredom. She contemplates an affair with a rakish spy, only to discover a world of intrigue and treachery that she never knew existed. Even more shocking, her neglectful husband is suddenly very attentive—quite the jealous type—and apparently there is much more to him than she ever knew. Lord and Lady Spy Trilogy: Lord and Lady Spy (Book 1) True Spies (Book 2) Love and Let Spy (Book 3) Praise for Shana Galen: "Galen strikes the perfect balance between dangerous intrigue and sexy romance."—Booklist "A thrilling ride, filled with mystery, intrigue and romance."—Fresh Fiction on If You Give a Duke a Diamond